Curriculum enrichment for the superior students in the Philippine high school - Sese, Rosa Fajardo 1932- (1967)
The objective of the study was to propose an enriched curriculum for the superior high school students in the Philippines in general and the superior students of the Pasay City High School in particular. For the purpose of the study, enrichment will be on the provision of additional materials and learning experiences to the superior students in addition to what is offered by the existing 2-2 Plan for public high schools.